How do you differentiate f(x)= (3x^2-5x+2)/ (x+1 ) using the quotient rule? Calculus Basic Differentiation Rules Quotient Rule 1 Answer Guilherme N. Jan 9, 2016 Quotient rule states that (a/b)'=(a'b-ab')/b^2 Explanation: Thus: (df(x))/(dx)=((6x-5)(x+1)-(3x^2-5x+2)(1))/(x+1)^2 (df(x))/(dx)=(6x^2+x-5-3x^2+5x-2)/(x+1)^2 (df(x))/(dx)=(3x^2+6x-7)/(x+1)^2 Answer link Related questions What is the Quotient Rule for derivatives? How do I use the quotient rule to find the derivative? How do you prove the quotient rule? How do you use the quotient rule to differentiate y=(2x^4-3x)/(4x-1)? How do you use the quotient rule to differentiate y=cos(x)/ln(x)? How do you use the quotient rule to find the derivative of y=tan(x) ? How do you use the quotient rule to find the derivative of y=x/(x^2+1) ? How do you use the quotient rule to find the derivative of y=(e^x+1)/(e^x-1) ? How do you use the quotient rule to find the derivative of y=(x-sqrt(x))/(x^(1/3)) ? How do you use the quotient rule to find the derivative of y=x/(3+e^x) ? See all questions in Quotient Rule Impact of this question 2534 views around the world You can reuse this answer Creative Commons License